Tropical Rainfall Linked to Stronger Future ENSO‐NAO Teleconnection in CMIP5 Models. Issue 22 (16th November 2020) - Fereday, D. R.; Chadwick, R.; Knight, J. R.; Scaife, A. A.
Abstract: The El Niño–Southern Oscillation (ENSO) has previously been shown to influence the winter North Atlantic Oscillation (NAO). Here we investigate the ENSO‐NAO teleconnection in historical and RCP8.5 scenario CMIP5 simulations and show a future strengthening of the teleconnection under RCP8.5. The teleconnection strength is associated with increased East Pacific tropical rainfall variability. Stratospheric and tropospheric teleconnection pathways are examined, with both pathways having stronger links in the future. The stratospheric pathway involves the Aleutian Low and the stratospheric polar vortex with a downward influence on the NAO. This pathway is clearest in the high‐top models that better resolve the stratosphere. The tropospheric pathway is driven by the Pacific subtropical jet strengthening and extending further into the Atlantic in the future, generating increased baroclinicity in the Caribbean and influencing the Atlantic storm track. These results suggest increasing influence of tropical rainfall on extratropical circulation in the future. Plain Language Summary: Winter weather over Europe is driven by the North Atlantic Oscillation (NAO) an atmospheric circulation pattern linked to the fluctuating strength of westerly winds across the North Atlantic. Previous work has shown that the NAO is influenced by rainfall in the tropical East Pacific linked to the El Niño–Southern Oscillation (ENSO) an irregular warming and cooling of the tropical Pacific Ocean. We show that the ENSO‐NAO link strengthens in a future warmer climate according to climate models. Models with stronger links simulate bigger year‐to‐year changes in tropical east Pacific rainfall. We investigate two pathways in which the tropical rainfall influences the NAO. In the first pathway, the rainfall is linked to a persistent low‐pressure system over the North Pacific; this then weakens the winter stratospheric polar vortex, which in turn affects the NAO. The models that best simulate the stratosphere show this pathway is stronger in the future. In the second pathway, the jet stream over the Pacific extends further into the Atlantic in the future. This affects the Atlantic storm track, which is itself closely linked to the NAO. These results suggest that tropical rainfall has an increasing influence on the winter weather over Europe in the future, which may lead to better future predictability. Key Points: CMIP5 models show a stronger link between NAO and ENSO in the future under climate change Models with highest interannual tropical East Pacific rainfall variability show strongest effect Results show potential for increased seasonal predictability of the NAO in the future